2006
DOI: 10.1530/eje.1.02119
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rituximab treatment for thyroid-associated ophthalmopathy as a result of intraorbital B-cell depletion in one patient unresponsive to steroid immunosuppression

Abstract: One patient with Graves' hyperthyroidism and ophthalmopathy in its active phase and unresponsive to steroid, was treated with the anti-CD20 monoclonal antibody, rituximab (RTX), as part of an open study. The effect of RTX in the thyroid and the orbital tissues was studied. The ophthalmopathy responded to RTX therapy by ameliorating the eye signs with a decrease in the clinical activity score from 5 to 2 in 3 months, while the patient had peripheral B-cell depletion. Hyperthyroidism did not improve during the 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 30 publications
4
91
1
2
Order By: Relevance
“…Alternatively, RTX has been shown to interfere with the production of inflammatory cytokines and with B cell-driven antigen presentation (7), suggesting that RTX might be indirectly responsible for the depletion of autoreactive T cells also. Lack of T cell infiltration after B cell depletion with RTX has been reported in the orbital tissues of patients with GO (3,10), suggesting that this might be a likely mechanism for its effect. Preliminary studies have suggested that RTX can be effective either as first-line treatment for moderateto-severe GO or as additional therapy in patients resistant to intravenous steroids (6).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Alternatively, RTX has been shown to interfere with the production of inflammatory cytokines and with B cell-driven antigen presentation (7), suggesting that RTX might be indirectly responsible for the depletion of autoreactive T cells also. Lack of T cell infiltration after B cell depletion with RTX has been reported in the orbital tissues of patients with GO (3,10), suggesting that this might be a likely mechanism for its effect. Preliminary studies have suggested that RTX can be effective either as first-line treatment for moderateto-severe GO or as additional therapy in patients resistant to intravenous steroids (6).…”
Section: Introductionmentioning
confidence: 92%
“…Rituximab (RTX), a chimeric mouse-human monoclonal antibody directed against the CD 20 antigen on B lymphocytes, has been associated with very encouraging responses in treating patients with active moderate-tosevere GO since 2006 (1,2,3). B cell depletion induced by RTX may affect pathogenic TSH-R autoantibody or directly interfere with B cells' antigen-presenting cell function (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Following the first report on a successful treatment of one patient with moderate-to-severe GO (107), several noncontrolled studies on the effects of rituximab (RTX) in GO have appeared in the literature (108). More recently, two randomized controlled trials in moderateto-severe GO comparing RTX with placebo (109) and to steroids (110), respectively, have just been published.…”
Section: Rituximabmentioning
confidence: 99%
“…In earlier reports (107,114), RTX has been employed in patients with active steroid-resistant GO. In an open study, RTX has subsequently been used as a first-line therapy in previously untreated patients (115).…”
Section: Efficacy and Dosing Of Rtx In Gomentioning
confidence: 99%
See 1 more Smart Citation